Infant antibody and B-cell responses following confirmed pediatric GII.17 norovirus infections functionally distinguish GII.17 genetic clusters - Strother, Camilla A.; Brewer-Jensen, Paul D.; Becker-Dreps, Sylvia; Zepeda, Omar; May, Samantha; Gonzalez, Fredman; Reyes, Yaoska; McElvany, Benjamin D.; Averill, April M.; Mallory, Michael L.; Montmayeur, Anna M.; Costantini, Verónica P.; et al. (Frontiers in Immunology, 2023)
Genogroup II (GII) noroviruses are a major cause of diarrheal disease burden in children in both high- and low-income countries. GII.17 noroviruses are composed of distinct genetic clusters (I, II, IIIa, and IIIb) and have shown potential for replacing historically more prevalent GII.4 strains, but the serological basis for GII.17 antigenic diversity has not been studied in children. Utilizing samples from a birth cohort, we investigated antibody and B-cell responses to GII.17 cluster variants in confirmed GII.17 infections in young children as well as demonstrated that the distinct genetic clusters co-circulate. Polyclonal serum antibodies bound multiple clusters but showed cluster-specific blockade activity in a surrogate virus neutralization assay. Antibodies secreted by immortalized memory B cells (MBCs) from an infant GII.17 case were highly specific to GII.17 and exhibited blockade activity against this genotype. We isolated an MBC-derived GII.17-specific Immunoglobulin A (IgA) monoclonal antibody called NVA.1 that potently and selectively blocked GII.17 cluster IIIb and recognized an epitope targeted in serum from cluster IIIb–infected children. These data indicate that multiple antigenically distinct GII.17 variants co-circulate in young children, suggesting retention of cluster diversity alongside potential for immune escape given the existence of antibody-defined cluster-specific epitopes elicited during infection.